Efficacy of Feeding Ensiled Corn Crop Residues to Sheep - Elkholy, M.El.H.; Hassanein, El.I.; Soliman, M.H.; Eleraky, Wafaa; Elgame, M.F.A.; Ibraheim, Dohaa (Pakistan Journal of Nutrition, 2009)
Chemical composition and silage quality of corn by-products silage were determined. Nutritive value was also investigated through digestibility trials and ruminal parameters (pH, TVFA`S and ammonia-nitrogen concentration). The effect of feeding the experimental diets on some blood metabolites as glucose, total protein, albumin, globulin, total lipids, triglycerides, cholesterol and BUN (Blood Urea Nitrogen) was also studied. Six healthy Baladi rams, were design to 3 different ration (control group A, fed concentrate mixture and (berseem hay), group B, fed concentrates mixture and 4% urea treated corn silage + 3% molasses and group C, fed concentrates mixture and 2% yeast treated corn silage + 3% molasses. Results revealed that Crude protein contents of treated corn silage by urea or yeast with molasses were increased. EE and Ash content as well as Crude fiber fractions (CF, ADF and NDF) were decreased due to ensilage. At the time of the feeding the pH, the total volatile fatty acids (meq/100 g DM) and the NH3-N as % of total nitrogen values of treated corn silage by urea or yeast with molasses were (4.2 and 3.85 ), (2.95 and 3.44) and (9.95 and 8.62) respectively which indicate good quality silage. Significant decrease in feed intake of group (B and C). Digestion Coefficient values of DM of group (B) were significantly decreased while for group (C) there are non significant difference .Digestion Coefficient values of OM and CP of group (B and C) were significantly increased. Digestion Coefficient values of EE did not show any significant difference in group (B) and significantly increased in group (C).Digestion Coefficient values of NFE and crude fiber fractions (CF, ADF and NDF), Total digestible nutrients and Digestible crude protein were significantly increased in group (B and C). The pH values were non significantly changed in group (B) and significantly decreased in group (C) at zero time. These values were significantly increased in group (B) and non significantly changed in group (C) at 3 and 6 hours post feeding. The peak of ruminal Total VFA and ammonia nitrogen concentration values reached after 3 h post-feeding in all groups. Blood glucose, total protein, albumin, globulin and BUN (Blood urea Nitrogen) were increased in groups (A and B). Total lipids, total cholesterol and triglycerides were decreased in groups (A and B), but the decrease was more in group (C) compared with the control.